Gothikana - RuNyx (Novelist) (Tom Doherty Associates/Tor Publishing Group, 2024)
"An outcast her entire life, Corvina Clemm is left adrift after losing her mother. When she receives the admission letter from the mysterious University of Verenmore, she accepts it as a sign from the universe. The last thing she expects though is an old, secluded castle on top of a mountain riddled with secrets, deceit, and death. An enigma his entire life, Vad Deverell likes being a closed book but knowing exactly everything that happens in the university. A part-time professor working on his thesis, Vad has been around long enough to know the dangers the castle possesses. And he knows the moment his path crosses with Corvina, she's dangerous to everything that he is. They shouldn't have caught each other's eye. They cannot be. But a chill-inducing century-old mystery forces them to collide. People have disappeared every five years over the past century, Corvina is getting clues to unraveling it all, and Vad needs to keep an eye on her. And so begins a tale of the mysterious, the morbid, the macabre, and a deep love that blossoms in the unlikeliest of places."--Amazon.